The Blade of the Youngest Princess: The Eastern Kalimantan Folklore in the Analysis of Vladimir Propp’s Narrative Structure - Siti Hafsah (Universitas Cokroaminoto Palopo, 2018)
The object of this research is The Blade of the Youngest Princess folklore (which abbreviated KLPB – Kepala Lading Putri Bungsu) from East Kalimantan. The researcher uses an approach of Vladimir Propp’s Narrative Structure to analyze the folklore. This research aims to reveal the function of the system of structure in folklore. The research uses qualitative methods and narrative structure of Vladimir Propp is used as an approach to identify the function and the structure of the story to reveal various values in community in East Kalimantan especially the moral value and the educational value. From the analysis, researcher finds that from the perspective of characters’ function, the folklore is formed from fifteen function. Whereas the elements of value of the community especially in East Kalimantan as reflected from the folklore is that the king is wise, fair, and a good decision maker.